Irish Identity in the Plays by Brian Friel - Šramhauserová, Petra (Univerzita Pardubice, 2012)
The main subject of this paper is the analysis of Irish identity in two plays by Brian Friel, Translations and The Home Place. The initial part introduces Brian Friel as a co-founder of the Field Day Theatre Company and its significance for Friel's writing. Furthermore, the definition of identity and nation is provided. Then, the role of language and sense of home as key features of identity and Friel's plays are described as well as the outline of historical events reflected in the analysed plays is drawn. The following part comprises the actual analysis of the pieces of drama. The analysis focuses on the significant elements of Irish identity reflected in the plays, specifically in characters' deeds and attitudes. Despite the juxtaposition of two seemingly different works written in twenty-five years interval, a lot of similarities and identity aspects are compared and finally summarized in the conclusion.
Irská identita v dramatu Briana Friela
Keywords: národní identita; jazyk; historie; narušení; hrozba; střet; domov; dilema; translations; home place; Friel, Brian; Field Day; national identity; language; history; intrusion; threat; conflict; home place; dilemma